ZIF-67 metal-organic frameworks synthesized onto CNT supports for oxygen evolution reaction in alkaline water electrolysis. (20th January 2023) - Jung, Hye Bin; Kim, Youngjun; Lim, Jiyeon; Cho, Sungwon; Seo, Myeongmin; Kim, Ik-Sun; Kim, MinJoong; Lee, Changsoo; Lee, Young-Woo; Yoo, Chung-Yul; Oh, Yoogyeong; Hong, Jinkee; et al.
Highlights: ZIF-67 are synthesized onto CNT support for electrocatalyst of water electrolysis. Optimal ZIF-67@CNT catalyst condition for the best OER performance is investigated. ZIF-67@CNT shows a highly long-term stability under dynamic operating condition. Abstract: Oxygen evolution reaction (OER) is one of the key half-reaction in water-splitting hydrogen production and metal-air/metal-oxygen batteries. In this study, we synthesized CNT-supported ZIF-67 metal-organic frameworks (MOFs) for an electrocatalyst for OER in alkaline water electrolysis. MOFs have superior advantages as electrochemical catalysts such as well-defined molecular crystal structure, high surface area, isolated active metal center, and versatile material choice and tunability. However, the low electrical conductivity of coordinated organic ligands limits the full utilization of the merits of MOFs in electrochemical applications. Here, ZIF-67 was synthesized onto highly conductive carbon nanotubes (CNTs) to increase the electrical conductivity of the ZIF-67 OER catalyst in alkaline WE. The prepared ZIF-67@CNT showed excellent electro-activity in an optimized experimental condition. It exhibited a low overpotential of 285 mV at a current density of 10 mA/cm 2 with a Tafel slope of 57 mV/dec, representing the faster charge transfer reaction and kinetics of OER. In addition, it showed highly stable and durable long-term electroactivity during harsh operating conditions due to the morphological characteristic of the ZIF-67@CNT catalyst, offering a practical future hydrogen production system integrated with unstable renewable energy sources. Graphical abstract: Image, graphical abstract